2010
DOI: 10.1007/s10549-010-0788-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase III randomized trial of sunitinib versus capecitabine in patients with previously treated HER2-negative advanced breast cancer

Abstract: This multicenter, randomized, open-label phase III trial (planned enrollment: 700 patients) was conducted to test the hypothesis that single-agent sunitinib improves progression-free survival (PFS) compared with capecitabine as treatment for advanced breast cancer (ABC). Patients with HER2-negative ABC that recurred after anthracycline and taxane therapy were randomized (1:1) to sunitinib 37.5 mg/day or capecitabine 1,250 mg/m2 (1,000 mg/m2 in patients >65 years) BID on days 1–14 q3w. The independent data-moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(96 citation statements)
references
References 22 publications
2
94
0
Order By: Relevance
“…Figure 1 outlined the selection process in detail. These trials represented three studies with sorafenib, 21,31,32 three with sunitinib, 20,33,34 three with vandetanib [35][36][37] and five with pazopanib. 2,[38][39][40][41] The characteristics of each included trial were presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 outlined the selection process in detail. These trials represented three studies with sorafenib, 21,31,32 three with sunitinib, 20,33,34 three with vandetanib [35][36][37] and five with pazopanib. 2,[38][39][40][41] The characteristics of each included trial were presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Recent trials evaluating new regimens for breast cancer, particularly with molecular-targeted drugs, have thus tended to target specific subtypes to overcome the limited effects of conventional drugs and to examine new approaches to effectively suppressing the function of specific molecules that are critical for tumor growth and survival. Some negative studies using new molecular-targeted medicines have already been reported because of not meeting the trial end points for the prolongation of progression-free or overall survival [20,21]. These setbacks may be attributable to the dilution of clinical benefits by prolonged survival after progression due to other drugs, ethical limitations on clinical trials allowing cross-over administration of experimental medicines and poor cost-benefit ratios with expensive new molecular-targeted medicines [22].…”
Section: Discussionmentioning
confidence: 99%
“…Sunitinib was unable to provide any benefit either as monotherapy compared to capecitabine or in combination with chemotherapy [49,[51][52][53]. There are no specific data for triplenegative patients from these trials.…”
Section: Anti-angiogenesismentioning
confidence: 99%